Cold War captives : imprisonment, escape, and brainwashing - Carruthers, Susan L. (Susan Lisa) (University of California Press, 2009)
Susan Carruthers offers a provocative history of early Cold War America, in which she recreates a time when World War III seemed imminent. She shows how central to American opinion at the time was a fascination with captivity & escape. Captivity became a way to understand everything.